2021
DOI: 10.21608/aujes.2021.89948.1035
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of degradation in the Tropical Environment: Causes, Footprints and Remedies

Abstract: One of the challenges that pose threats to human survival in these contemporary times is environmental degradation. The over-exploitation of natural resources is currently at an alarming rate in developing nations with an unabated population increase like Nigeria and may continue to spell hardship and discomfort if efforts are not made by all stakeholders to checkmate the trend. The rate at which the human population is increasing also needs to be checked in order to ensure sustainable availability of environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Even though, bats could be found to be detrimental to human environment, its benefits outweighed the negatives. 2 , 36 , 39 , 40 …”
Section: Resultsmentioning
confidence: 99%
“…Even though, bats could be found to be detrimental to human environment, its benefits outweighed the negatives. 2 , 36 , 39 , 40 …”
Section: Resultsmentioning
confidence: 99%
“…These challenges, in a human environment, are still on the rise in view of the unabated growth in population and urbanization, and the increase in food insecurity, among others, especially in the underdeveloped countries of the world. 12 – 14 Agbonifo 15 and Unigwe and Egbueri 9 noted the grievous impact of environmental resources on pollution, especially on the socioeconomic status of the society which was associated with the poverty level, poor health status, unemployment, population displacement and migration, and insecurity, among others in the Niger Delta region of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Coccia 10 reported that income disparity in their respective study areas made significant improvements in the control of air pollution. In addition, the impact of religious activities on air and noise pollution had been reported 11 , 12 while 13 , 14 investigated the impact of change in household environment condition on morbidity in India. All these poor attitude and inactions against the natural environment have partly resulted in dwindling human health, death, and economic downturn in most of these countries.…”
Section: Introductionmentioning
confidence: 99%